Relationship analysis and genetic diversity of tea Camellia sinensis germplasm from illegitimate seeds based on morphological characters - YUDITHIA MAXISELLY; CITRA BAKTI; MURGAYANTI MURGAYANTI; ERNAH ERNAH; ABDILLAH AZZAM WAHYUDIN; MUHAMAD KHAIS PRAYOGA; AGUNG KARUNIAWAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Maxiselly Y, Bakti C, Murgayanti, Ernah, Wahyudin AA, Prayoga MK, Karuniawan A. 2024. Relationship analysis and genetic diversity of tea Camellia sinensis germplasm from illegitimate seeds based on morphological characters. Biodiversitas 25: 3486-3495. Tea (Camellia sinensis (L.) O. Kuntze) is a plant with self-incompatible traits and requires significant efforts to assemble superior clones. The generation of the superior clone is from seed-derived genetic material that demands comprehensive information on population variance, genetic diversity, and the level of relationship among accessions. Therefore, this research aimed to determine population variances, genetic diversity, and relationships of tea germplasm accessions based on morphological characteristics. The experiment was conducted from August 2023 to January 2024 at the Indonesian Research Institute Tea and Cinchona, Mekarsari Village, Pasir Jambu District, Bandung Regency, West Java, Indonesia. An experimental method, "no layout design," was used to identify morphological traits of 36 characters in 50 selected accessions from the population. Observational data were analyzed to determine variance values, principal component analysis (PCA), heatmap correlation, and cluster analysis using XLSTAT software. The results showed a wide variation of 50% among the 36 characters, with genetic diversity in the 2 Principal Components (PC) at 38.99%. The cluster analysis of accessions had an Euclidean distance range, measuringa measure of the straight line distance between two points of 2.23 to 12.86. This variation was caused by a high correlation of some characteristics, such as leaf length, width, and leaf area, as the potential to develop the new tea clone.